ANALISIS KUALITATIF REKAM MEDIS ELEKTRONIK PENDAFTARAN PASIEN RAWAT JALAN DI RSUD IBNU SINA GRESIK: Qualitative Analysis of Electronic Medical Records of Outpatient Registration at Ibnu Sina Gresik Hospital - Prisusanti, Retno Dewi; Ratnasari, Dwi; Nabelah, Putri vinata (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
This research examines the implementation of Electronic Medical Records (RME) in the outpatient registration process at Ibnu Sina Gresik Regional Hospital. Using qualitative research methods with a case study approach, this research involved in-depth interviews and direct observation of the use of RME by medical and administrative personnel. The results show that the implementation of RME at Ibnu Sina Gresik Regional Hospital provides a number of significant benefits, such as increased operational efficiency, better diagnostic accuracy, and reduced data input errors. However, challenges such as staff adaptation to new technology and system integration remain major concerns. Continuous evaluation is needed to ensure that the full potential of RME can be utilized to improve the quality of health services and overall patient satisfaction at RSUD Ibnu Sina Gresik.